Serum triglycerides level is independently associated with renal outcomes in patients with non-dialysis chronic kidney disease: Results from KNOW-CKD study - Suh, Sang Heon; Oh, Tae Ryom; Choi, Hong Sang; Kim, Chang Seong; Bae, Eun Hui; Oh, Kook-Hwan; Han, Seung Hyeok; Ma, Seong Kwon; Kim, Soo Wan (Frontiers in Nutrition, 2022)
To investigate whether high serum triglycerides (TG) level is associated with adverse renal outcomes in patients with non-dialysis chronic kidney disease (CKD), a total of 2,158 subjects from a prospective cohort study (Korean Cohort Study for Outcome in Patients With Chronic Kidney Disease) were divided into the quartile by serum TG level. The primary outcomes were composite renal events, which is defined as a composite of decline of kidney function (the first occurrence of > 50% decline of estimated glomerular filtration rate or doubling of serum creatinine from the baseline) or onset of end-stage renal disease (initiation of dialysis or kidney transplantation). During the median follow-up of 6.940 years, the cumulative incidence of composite renal event was significantly differed by serum TG level in Kaplan–Meier curve analysis (P < 0.001, by Log-rank test). Cox regression analysis demonstrated that, compared to that of the 1st quartile, the risk of composite renal event was significantly higher in the 4th quartile (adjusted hazard ratio 1.433, 95% confidence interval 1.046 to 1.964). The association between high serum TG level and adverse renal outcome remained consistent in the cause-specific hazard model. Subgroup analyses revealed that the association is modified by age, estimated glomerular filtration rate, and spot urine albumin-to-creatinine ratio. In conclusion, high serum TG level is independently associated with adverse renal outcomes in patients with non-dialysis CKD. Interventional studies are warranted to determine whether lowering serum TG levels may alter the natural course of CKD.